Pengaruh Aktiva Tetap Terhadap Kemampulabaan Perusahaan : Studi Kasus Pada Kelompok Emiten Perusahaan Properti dan Real Estet. - Munawar, Aang; Hoerudin, Hoerudin (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2010)
In general, companies have the same goal and objectives, namely being successful and there after they develop more and get maximum profit. To achieve maximum profit, the companies use of various ways, one of them is by means rotation and processing of fixed assets owned by the companies and utilizing as a part of companiesâ operationalization. Therefore, the companies must be able to control the fixed assets in order to achieve their goals. When the fixed assets rotate and are used optimally in the companiesâ operationalization, they can be expected to support the companies in increasing their revenue. The companies can be said as successful when they get profit more and more. So does the rotation of assets, it well be said good if the companies perform fixed assets rotation gets increased. Profitability constitutes net final result of various decisions and policies of management with the result that profitability becomes criterion of success in achieving the companiesâ goal. The purpose of this research is to find out whether fixed assets rotation as a part of the companiesâ operationalization ha influence towards their profitability. This research forms analysis from finance report of the companies, that is from their balance report and profit and loss report. The result of this research by regression analysis shows that fixed assets had little influence toward the companiesâ profitability, that is as high as 0,8%, while the rest was influenced by other factors as high as 99,2%. The yield of evaluation shows that fixed assets at the companies operating in property and real estate field did not influence the companiesâ profitability. In general, fixed assets rotation of the six property and real estate companies got increased. The six companiesâ profitability got increases as well.